1982
DOI: 10.1136/hrt.48.6.584
|View full text |Cite
|
Sign up to set email alerts
|

Sinus node function in first three weeks after cardiac transplantation.

Abstract: SUMMARY Donor sinus node function was studied in 10 patients from day 4 to day 24 after cardiac transplantation. Cycle length, atrial arrhythmias, corrected sinus node recovery time, and estimated sinoatrial conduction time were recorded daily. Five patients had at least two sets of results suggesting sinus node dysfunction (group A) while five patients had no such abnormalities (group B). The prognosis in group A was poor, with four of the five patients dying within four months ofthe operation; one unexpected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…However, since intravascular ultrasound, a more sensitive indicator of vasculopathy than angiography, was not used to document evidence of chronic rejection, we cannot exclude the possibility that early bradycardia may have an impact in the development of allograft vasculopathy. Our results extend the findings of other studies that have shown that perioperative bradycardia is not associated with rejection within the first months after transplantation (1,7,19). The data also agree with the study by Heinz et al which demonstrated that bradycardia was not associated with a decreased survival several years after transplantation (9).…”
Section: Discussionsupporting
confidence: 93%
“…However, since intravascular ultrasound, a more sensitive indicator of vasculopathy than angiography, was not used to document evidence of chronic rejection, we cannot exclude the possibility that early bradycardia may have an impact in the development of allograft vasculopathy. Our results extend the findings of other studies that have shown that perioperative bradycardia is not associated with rejection within the first months after transplantation (1,7,19). The data also agree with the study by Heinz et al which demonstrated that bradycardia was not associated with a decreased survival several years after transplantation (9).…”
Section: Discussionsupporting
confidence: 93%
“…Local trauma to the superior vena cava, donor age, inadequate denervated heart response to vasoactive amines and previous use of antiarrhythmic drugs, especially amiodarone, may be involved 4,5,8,9,11,12,13,17,23 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies in retransplantation or necropsy have shown that cardiac conduction tissue is a specific target related to allograft rejection 13 . The arteries to sinoatrial and atrioventricular tissue are frequently involved in both an acute cellular reaction and in the chronic intimal fibro-cellular rejection reaction, causing sinus node dysfunction 24 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations